Booklet Sebagai Media Edukasi Untuk Meningkatkan Pengetahuan Remaja Putri Tentang Anemia - Masta Hutasoit; Yanita Trisetiyaningsih; Khristina Diaz Utami (Faletehan Health Journal, 2023)
Anemia is a nutritional problem that is often experienced by teenage girls and can decrease their reproductive health, motoric and mental development, learning achievement, fitness level, and unreached maximum height. Anemia in teenage girls is caused by a lack of nutrients consumed, especially iron and folic acid, which one of the reasons is the low level of knowledge and misperceptions related to diet. This study aimed to determine the effects of booklet on the increase of teenage girls’ knowledge of anemia. The method used was quasy experiment and a design of pretest-posttest without control group. The sample size was 57 teenage girls as respondents who were selected by purposive sampling. The respondents got a pretest, education by booklet, and a posttest. The results showed that the mean of pretest was 56.33, the minimum score of 37, and the maximum score of 85. While the mean of posttest was 86.67, the minimum score of 56, and the maximum score of 100. The data analysis by Wilcoxon test obtained a p value of 0.001. There were effects of health education by booklet on the increase of teenage girls’ knowledge of anemia. To conclude, booklet as a media of health education significantly impacts on the increase of teenage girls’ knowledge.